Public Participation for 21st Century Democracy - Nabatchi, Tina (Bryson Series in Public and Nonprofit Management, 2015)
A comprehensive text on the theory and practice of public participation Written by two leaders in the field, Public Participation for 21st Century Democracy explores the theory and practice of public participation in decision-making and problem-solving. It examines how public participation developed over time to include myriad thick, thin, and conventional opportunities, occurring in both face-to-face meetings and online settings. The book explores the use of participation in various arenas, including education, health, land use, and state and federal government. It offers a practical framework for thinking about how to engage citizens effectively, and clear explanations of participation scenarios, tactics, and designs. Finally, the book provides a sensible approach for reshaping our participation infrastructure to meet the needs of public officials and citizens. The book is filled with illustrative examples of innovative participatory activities, and numerous sources for more information. This important text puts the spotlight on the need for long-term, cross-sector, participation planning, and provides guidance for leaders, citizens, activists, and others who are determined to improve the ways that participation and democracy function. Public Participation for 21st Century Democracy: Helps students and practitioners understand the history, theory, and practice  of public participation Contains a wealth of case studies that explore the application of public participation in different settings Covers vital issues such as education, health, land use, and state and federal government Has accompanying instructor resources, such as PowerPoint slides, discussion questions, sample assignments, case studies and research from www.participedia.net, and classroom activities.